Ascospore release in apple scab underlies infrared sensation. Issue 12 (December 2017) - Ehlert, Katja; Piepenbring, Meike; Kollar, Andreas
Abstract: The agent of apple scab disease ( Venturia inaequalis ) is the most common pathogen in apple cultivation. Its ascospores are released in spring, mainly during daylight hours and triggered by rain events. To investigate the causes of diurnal rhythm of ascospore dissemination of the apple scab fungus ascospore releases were examined continuously with spore traps in the orchard and with laboratory assays. One of the spore traps was illuminated at night with different light sources in each year during 2011–2015. The laboratory assays were performed with different light sources with varying wavelengths and intensities. In field and laboratory conditions only light including infrared radiation stimulated ascospore release, but not with light in the visible spectrum only. Artificial illumination during night was correlated with an increase of up to 46 % of ascospores released overnight in the field. We proved that infrared radiation induces V. inaequalis to release its spores. This is the first report in which spore discharge could be stimulated during night under field conditions.